High-proton-conduction and high-durability fuel cell proton membrane and preparation method thereof

The fuel cell proton membrane was prepared by a two-step dispersion process, which solved the problems of durability and proton conductivity of the existing proton membrane under chemical and mechanical stresses, and achieved a proton membrane with high proton conductivity and high durability.

CN119650747APending Publication Date: 2025-03-18UNILIA (SHANGHAI) FUEL CELLS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909554.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing fuel cell proton membranes are prone to failure of local pinholes and bulging under chemical attack and mechanical stress, resulting in a decrease in durability and proton conductivity.

Method used

The free radical quencher and stabilizer are dispersed in different liquid phase solvents by using a two-step dispersion process, and a uniformly dispersed sol structure is formed by mixing ultrasonic and stirring. Then, it is dispersed with the ionomer solution through film shearing to prepare a proton film with a reinforcing layer.

Benefits of technology

The high proton conductivity and durability of the proton membrane are achieved, which significantly reduces the amount of radical quenching agent added, and improves the mechanical stability and chemical durability of the proton membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention provides a high-proton-conduction and high-durability fuel cell proton membrane and a preparation method thereof, and belongs to the technical field of proton membranes. Comprising the following steps: S1, weighing a free radical quenching agent and a first solvent, stirring and mixing, and carrying out ultrasonic dispersion to obtain a first dispersion liquid; s2, weighing a stabilizer and a second solvent, stirring in a nitrogen protective atmosphere, then keeping stirring, carrying out microwave heating and reflux reaction, injecting the first dispersion liquid, and continuously mixing and stirring to obtain first sol; s3, dispersing the first sol and the ionomer solution through thin film shearing to obtain a to-be-coated film solution; s4, preparing the proton membrane with an enhancement layer from the membrane solution through a solution membrane forming method. The proton membrane preparation technology is simple and easy to operate, the equipment cost and the maintenance cost are low, and industrial continuous mass production is easy to achieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of proton membranes, and in particular to a proton membrane for a fuel cell with high proton conductivity and high durability and a preparation method thereof. Background Art

[0002] The widespread application of polymer electrolyte membrane fuel cell (PEMFC) technology is currently hindered by the insufficient durability of membrane electrode components and the high cost of raw materials. In the process of converting chemical energy into electrical energy in the fuel cell system, on the one hand, the active free radical groups generated by the electrochemical reaction will continuously attack the fragile functional groups in the ionomers constituting the proton membrane and the ionomers constituting the catalyst layer, which will reduce the thickness of the proton membrane or the catalyst layer and cause the proton membrane to produce local pinholes, bulges and other failure forms, thereby releasing hydrofluoric acid (HF), sulfuric acid (H2SO4) and fluorinated polymers into the exhaust gas; at the same time, it increases the possibility of reactant gases crossing on both sides of the anode and cathode, exposing the single cell to the risks of local short circuit and high-temperature burn-through. On the other hand, due to the limitation of the system BOP hardware, the wet heat cycle generates mechanical stress, resulting in physical damage to the proton membrane in the form of cracks, tears and pinholes. In the actual operation of the fuel cell system, the membrane electrode is subjected to chemical attack and mechanical stress at the same time, which leads to the synergistic effect between the above two degradation modes of the proton membrane, further accelerating the failure of the reliability and durability of the proton membrane.

[0003] Usually, the industry uses Ce as a free radical scavenger to extend the chemical durability of the proton membrane. The rapid regeneration redox reaction between Ce ions and free radicals can quench the free radicals generated by the oxygen reduction side reaction. However, the cerium ion nanocrystals are small in size and are mobile between ionomer molecules, which will cause the Ce ion effect to be short-lasting. At the same time, Ce ions, as a cation, occupy the proton conduction channel and reduce the proton conductivity of the proton membrane. Therefore, it is very necessary to develop a structure that can retain the function of Ce ion quencher and at the same time take into account the continuous establishment of proton transmission channels between ionomer molecules. Summary of the invention

[0004] The purpose of the present invention is to provide a high proton conductivity and high durability fuel cell proton membrane and a preparation method thereof. The preparation process is simple and easy to operate, the equipment cost and maintenance cost are low, and it is easy to realize industrial continuous mass production.

[0005] The technical solution of the present invention is achieved in this way:

[0006] The present invention provides a method for preparing a proton membrane of a fuel cell with high proton conductivity and high durability, which is characterized by comprising the following steps:

[0007] S1: weighing a free radical quencher and a first solvent, stirring and mixing, and ultrasonically dispersing to obtain a first dispersion;

[0008] S2: weighing a stabilizer and a second solvent, stirring and mixing them for a certain period of time under a nitrogen atmosphere, then stirring and heating, and after a certain period of reflux reaction, injecting the first dispersion liquid, and continuing to mix and stir to obtain a first sol;

[0009] S3: dispersing the first sol and the ionomer solution by thin film shearing to obtain a film solution to be coated;

[0010] S4: preparing a proton membrane with a reinforcement layer by a solution-based membrane formation method using the membrane solution.

[0011] As a further improvement of the present invention, the ultrasonic power in step S1 is 200-1000 W, the ultrasonic frequency is 10-30 kHz, and the ultrasonic duration is 1-30 min.

[0012] As a further improvement of the present invention, the free radical quencher in step S1 is one or more of cerium oxide, cerium sulfate, cerium carbonate, cerium nitrate, manganese oxide, manganese dioxide, and manganese trioxide, wherein the amount of metal added is 0.001%-2% of the dry components of the ionomer resin; and the first dispersion liquid is one or more of butanone, ethylene glycol, glycerol, and oleylamine.

[0013] As a further improvement of the present invention, the added amount of the metal is 0.01%-1% of the dry components of the ionomer resin.

[0014] As a further improvement of the present invention, the stirring and mixing speed in step S2 is 100-300 rpm, and the stirring and mixing time is 5-60 min; the heating is to heat the reactor from room temperature to 50-400 ° C at a heating rate of 1-10 ° C / min; the reflux reaction time is 10-20 min; the injection speed of the first dispersion is 1-20 ml / min, and the continued mixing and stirring time is 5-120 min.

[0015] As a further improvement of the present invention, the stabilizer in step S2 is one or more of sulfonated polystyrene, sulfonated polyvinyl pyrrolidone, and sulfonated carboxymethyl fiber, and the sulfonation degree of the stabilizer is 10-50%; the added amount of the stabilizer is 0.001%-0.01% of the dry components of the ionomer resin; and the second solvent is one or more of acetone, diethanolamine, dimethylformamide, dimethyl sulfoxide, and tetrahydrofuran.

[0016] As a further improvement of the present invention, the solid content of the ionomer resin dry component in the ionomer solution in step S3 is 10-30%, the ion exchange equivalent is 0.7-1.3, the side chain is long, and the molecular weight distribution is 100,000-500,000. The solvent of the ionomer solution is one or more of ethanol, propanol, and deionized water; the shearing speed is 10-40m / s, the shearing residence time is 1-12h, and the solution film forming method is one or more of wire rod coating, slit coating, gravure printing, and comma coating.

[0017] As a further improvement of the present invention, in step S3, the volume mass ratio of the first sol to the ionomer solution is 1 mL:0.5-1.5 g.

[0018] As a further improvement of the present invention, the reinforcement layer in step S4 is one or more of PTFE, PVDF, PPS, PEEK, and PES; and the thickness of the reinforcement layer is 5-50 μm.

[0019] The present invention further protects a high proton conductivity and high durability fuel cell proton membrane prepared by the above preparation method.

[0020] The present invention has the following beneficial effects:

[0021] (1) A two-step dispersion process is used to disperse the free radical quencher and the stabilizer with a sulfonated structure in different liquid phase solvents, and then mixed and stirred to form a uniformly dispersed sol structure. The sol structure can achieve uniform distribution and stable existence of the subsequent free radical quencher in the proton exchange membrane, and optimize the risk of local durability defects of the proton membrane. When achieving the same chemical durability life, the amount of free radical quencher added can be significantly reduced, and the proton conductivity of the proton membrane can be improved;

[0022] (2) After systematic design and optimization, stabilizers with certain proton conductivity are screened, which can achieve the goal of not affecting the proton conductivity of the proton membrane after addition. At the same time, the rigid functional groups in the stabilizer can enhance the physical and mechanical strength of the proton membrane and improve the mechanical stability of the proton membrane;

[0023] (3) The two-step dispersion process of the present invention can obtain a three-dimensional sol structure in which the free radical quencher is evenly dispersed and the free radical quencher and the stabilizer are fully chelated. Within an appropriate dispersion speed and strength range, a film solution evenly distributed in the liquid-solid phase can be obtained, which lays a foundation for improving the durability and consistency of the product.

[0024] (4) The above-mentioned proton membrane preparation process is simple and easy to operate, with low equipment cost and maintenance cost, and is easy to realize industrial continuous mass production. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] S1: Weigh 17.5 mg of cerium oxide and 87.5 mL of butanone, and perform ultrasonic dispersion at an ultrasonic power of 700 W, an ultrasonic frequency of 20 kHz, and an ultrasonic duration of 20 min. The ultrasonic mode is a continuous ultrasonic mode of 5 s, followed by a 5 s pause cycle to obtain a first dispersion;

[0028] S2: 1.8 mg of sulfonated polyvinyl pyrrolidone and 18 mL of acetone were weighed and magnetically stirred in a three-necked flask under a nitrogen atmosphere at a stirring speed of 100 pm for 10 min. Then, microwave heating was performed while stirring was maintained. The reactor was heated from room temperature to 80°C at a heating rate of 8°C / min. After reflux reaction for 10 min, the reactor was naturally cooled to room temperature. Then, the first dispersion was injected into the three-necked flask at a speed of 10 ml / min. Mixing and stirring were continued for 30 min to obtain a first sol.

[0029] S3: 100 mL of the first sol and 100 g of a 20 wt% ionomer solution were dispersed by thin film shearing at a shear rate of 10 m / s and a shear residence time of 1 h to obtain a film solution to be coated;

[0030] S4: Coat the membrane solution to be coated on one side of the PTFE with a supporting backing film at a coating speed of 20 mm / s, and dry at 90°C for 20 min. Then tear off the backing film and coat the membrane solution on the other side at a coating speed of 20 mm / s and dry at 100°C for 20 min. Finally, anneal at 110°C for 20 min to obtain the proton membrane to be used.

[0031] Embodiment 2-8

[0032] The difference between Examples 2-8 and Example 1 is that the process parameters in the proton membrane preparation method are different, see Table 1 for details.

[0033] Table 1

[0034]

[0035]

[0036] Comparative Example 1

[0037] S1: 17.5 mg of cerium oxide, 87.5 mL of butanone, 1.8 mg of sulfonated polyvinyl pyrrolidone, and 18 mL of acetone were weighed and magnetically stirred in a three-necked flask under a nitrogen atmosphere at a stirring speed of 100 pm for 10 min. The reactor was then heated from room temperature to 80°C at a heating rate of 8°C / min while stirring. After reflux reaction for 10 min, the reactor was naturally cooled to room temperature to obtain the first sol;

[0038] S2: 100 mL of the first sol and 100 g of a 20 wt% ionomer solution were dispersed by thin film shearing at a shear rate of 10 m / s and a shear residence time of 1 h to obtain a film solution to be coated;

[0039] S3: Coat the membrane solution to be coated on one side of the PTFE with a supporting backing film at a coating speed of 20 mm / s and dry at 90°C for 20 min. Then tear off the backing film and coat the membrane solution on the other side at a coating speed of 20 mm / s and dry at 100°C for 20 min. Finally, anneal at 110°C for 20 min to obtain the proton membrane to be used.

[0040] Comparative Example 2

[0041] S1: Weigh 17.5 mg of cerium oxide and 87.5 mL of butanone, and perform ultrasonic dispersion at an ultrasonic power of 700 W, an ultrasonic frequency of 20 kHz, and an ultrasonic duration of 20 min. The ultrasonic mode is a continuous ultrasonic mode of 5 s, followed by a 5 s pause cycle to obtain a first dispersion;

[0042] S2: Weigh 1.8 mg of sulfonated polyvinyl pyrrolidone and 18 mL of acetone in a three-necked flask, then inject the first dispersion into the three-necked flask at a rate of 10 ml / min, mix and stir for 30 minutes to obtain a first sol;

[0043] S3: 100 mL of the first sol and 100 g of a 20 wt% ionomer solution were dispersed by thin film shearing at a shear rate of 10 m / s and a shear residence time of 1 h to obtain a film solution to be coated;

[0044] S4: Coat the membrane solution to be coated on one side of the PTFE with a supporting backing film at a coating speed of 20 mm / s, and dry at 90°C for 20 min. Then tear off the backing film and coat the membrane solution on the other side at a coating speed of 20 mm / s and dry at 100°C for 20 min. Finally, anneal at 110°C for 20 min to obtain the proton membrane to be used.

[0045] Comparative Example 3

[0046] S1: 17.5 mg of cerium oxide, 87.5 mL of butanone, 1.8 mg of sulfonated polyvinyl pyrrolidone, and 18 mL of acetone were weighed and magnetically mixed and stirred for 30 min in a three-necked flask under a nitrogen atmosphere to obtain a first sol;

[0047] S2: 100 mL of the first sol and 100 g of a 20 wt% ionomer solution were dispersed by thin film shearing at a shear rate of 10 m / s and a shear residence time of 1 h to obtain a film solution to be coated;

[0048] S3: Coat the membrane solution to be coated on one side of the PTFE with a supporting backing film at a coating speed of 20 mm / s and dry at 90°C for 20 min. Then tear off the backing film and coat the membrane solution on the other side at a coating speed of 20 mm / s and dry at 100°C for 20 min. Finally, anneal at 110°C for 20 min to obtain the proton membrane to be used.

[0049] Comparative Example 4

[0050] S1: 100 g of 20 wt% ionomer solution was dispersed by thin film shearing, with a shearing speed of 10 m / s and a shearing residence time of 1 h to obtain a film solution to be coated;

[0051] S2: Coat the membrane solution to be coated on one side of the PTFE with a supporting backing film at a coating speed of 20 mm / s and dry at 90°C for 20 min. Then tear off the backing film and coat the membrane solution on the other side at a coating speed of 20 mm / s and dry at 100°C for 20 min. Finally, anneal at 110°C for 20 min to obtain the proton membrane to be used.

[0052] Preparation method of membrane electrode: 0.5g of commercial 50% Pt / C catalyst powder was added to Nafion membrane solution containing 0.25g of ionomer and 40g of mixed solution of ethanol and water (Vethanol:Vwater=4:1), and dispersed at 1000rpm for 30min using a high-speed shear emulsifier. Then, an ultrasonic atomization sprayer was used to spray 0.40mg / cm on the cathode side of the prepared proton membrane. 2 , spraying loading on the anode side is 0.02mg / cm 2 After bonding the frame, carbon paper and packaging, the membrane electrode sample to be tested is obtained.

[0053] The durability test conditions adopt the U.S. Department of Energy test method as shown in Table 2

[0054] Table 2

[0055]

[0056]

[0057] The performance and durability characteristics of the proton membranes of Examples 1-8 and Comparative Examples 1-4 and the corresponding prepared membrane electrode (MEA) are summarized in Table 3.

[0058] Table 3

[0059]

[0060] Analysis of Tables 1-2 and 3 shows that the comparison of Examples 1-6 shows that in the preparation steps (1) and (2), the free radical quencher can be uniformly dispersed and the three-dimensional sol structure with sufficient chelation between the free radical quencher and the stabilizer can be obtained through the two-step dispersion process within an appropriate dispersion energy intake. The comparison of Examples 1, 7, and 8 shows that step (3) can obtain a membrane solution uniformly distributed in the liquid-solid phase within an appropriate dispersion speed and intensity range, which lays a foundation for improving the durability and consistency of the product.

[0061] Compared with Comparative Example 1, Comparative Example 3 does not have a heating step, and the performance of the proton membrane obtained is further reduced. It can be seen that the heating process has a significant improvement in improving the comprehensive performance of the proton membrane. Analysis of Example 1 and Comparative Examples 1-4 shows the necessity of constructing a stable, continuous, fully chelated three-dimensional sol structure between the free radical quencher and the stabilizer in the two-step dispersion process. Whether the free radical quencher or the stabilizer itself is not pre-dispersed first, the proton membrane obtained using the same downstream process will be greatly reduced in performance or durability. If the free radical quencher is not fully pre-dispersed, the performance drops by about 70mV. This is because the uneven distribution of free radicals will significantly affect the connectivity of the proton transport channels in the proton membrane, thereby deteriorating the membrane electrode water management ability, thereby affecting the membrane electrode performance and durability characteristics, and the chemical durability time is only 25% of that of the stable dispersion system. If the stabilizer is not pre-dispersed, the performance decreases by about 50mV, and the comprehensive durability is about 50% of the stabilized system. This is because the unanchored free radical quencher quickly migrates and dissolves under the flow field conditions brought about by the alternating dry-wet cycles, and cannot continue to carry out redox reactions to quench active free radicals, thereby failing to protect the proton membrane.

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a proton membrane for a fuel cell with high proton conductivity and high durability, characterized in that: The following steps are involved: S1: weighing a free radical quencher and a first solvent, stirring and mixing, and ultrasonically dispersing to obtain a first dispersion; S2: weighing a stabilizer and a second solvent, stirring and mixing them for a certain period of time under a nitrogen atmosphere, then stirring and heating, and after a certain period of reflux reaction, injecting the first dispersion liquid, and continuing to mix and stir to obtain a first sol; S3: dispersing the first sol and the ionomer solution by thin film shearing to obtain a film solution to be coated; S4: preparing a proton membrane with a reinforcement layer by a solution-based membrane formation method using the membrane solution.

2. The preparation method according to claim 1, characterized in that: In step S1, the ultrasonic power is 200-1000 W, the ultrasonic frequency is 10-30 kHz, and the ultrasonic duration is 1-30 min.

3. The preparation method according to claim 1, characterized in that: The free radical quencher in step S1 is one or more of cerium oxide, cerium sulfate, cerium carbonate, cerium nitrate, manganese oxide, manganese dioxide, and manganese trioxide, wherein the amount of metal added is 0.001%-2% of the dry components of the ionomer resin; the first dispersion is one or more of butanone, ethylene glycol, glycerol, and oleylamine.

4. The preparation method according to claim 3, characterized in that: The added amount of the metal is 0.01%-1% of the dry component of the ionomer resin.

5. The preparation method according to claim 1, characterized in that: The stirring and mixing speed in step S2 is 100-300 rpm, and the stirring and mixing time is 5-60 min; the heating is to heat the reactor from room temperature to 50-400 ° C at a heating rate of 1-10 ° C / min; the reflux reaction time is 10-20 min; the injection speed of the first dispersion is 1-20 ml / min, and the continued mixing and stirring time is 5-120 min.

6. The preparation method according to claim 1, characterized in that: In step S2, the stabilizer is one or more of sulfonated polystyrene, sulfonated polyvinyl pyrrolidone, and sulfonated carboxymethyl fiber, and the sulfonation degree of the stabilizer is 10-50%; the added amount of the stabilizer is 0.001%-0.01% of the dry component of the ionomer resin; and the second solvent is one or more of acetone, diethanolamine, dimethylformamide, dimethyl sulfoxide, and tetrahydrofuran.

7. The preparation method according to claim 1, characterized in that: The solid content of the ionomer resin dry component in the ionomer solution in step S3 is 10-30%, the ion exchange equivalent is 0.7-1.3, the side chain is long, and the molecular weight distribution is 100,000-500,000. The solvent of the ionomer solution is one or more of ethanol, propanol, and deionized water; the shearing speed is 10-40m / s, the shearing residence time is 1-12h, and the solution film forming method is one or more of wire rod coating, slit coating, gravure printing, and comma coating.

8. The preparation method according to claim 1, characterized in that: In step S3, the volume mass ratio of the first sol to the ionomer solution is 1 mL: 0.5-1.5 g.

9. The preparation method according to claim 1, characterized in that: The reinforcing layer in step S4 is one or more of PTFE, PVDF, PPS, PEEK, and PES; the thickness of the reinforcing layer is 5-50 μm.

10. A high proton conductivity and high durability fuel cell proton membrane prepared by the preparation method according to any one of claims 1 to 9.